Effect of Household Income on Household Welfare in Kitumba Sub-County Kabale District. - Kakuru, Richard (Kabale University, 2024)
The study examined the effect of household income on household welfare in Kitumba sub-county Kabale district. The objectives of the study were; to find out the effect of household income on the level of education in Kitumba sub-county Kabale District, to investigate the effect of household income on health accessibility in Kitumba sub-county Kabale District and to establish the effect of household income on food security in Kitumba sub-county Kabale District. A cross-sectional study design was used and data was collected using interviews and questionnaires. The study results on the effect of household income on the level of education in Kitumba sub-county Kabale District, the highest number of respondents mentioned that higher-income families have more options in selecting quality schools which can improve the level of education for their children while the least number of respondents mentioned that higher household income often correlates with jobs that allow parents time to be involved in their children’s education. In the study findings on the effect of household income on health accessibility in Kitumba sub-county Kabale District, the highest number of respondents mentioned that households with higher income are more likely to afford regular health check-ups, vaccinations, and preventive screenings, which can detect and address health issues early while the least number of respondents mentioned that higher-income households can more easily afford consultation fees, treatment costs, and surgical procedures, whereas lower-income families might struggle to pay for even basic healthcare services. The study findings on the effect of household income on food security in Kitumba sub-county Kabale District, the highest number of respondents mentioned that Higher-income households can afford a diverse diet, which is crucial for meeting nutritional needs as this includes access to fresh produce, meat, and dairy products, as well as fortified foods and the least number of respondents mentioned that income allows households to cope with seasonal variability in food availability by purchasing preserved or imported foods during off-seasons, ensuring consistent nutrition throughout the year. The study recommended that there should be implementation of financial literacy programs to educate households on managing finances, saving for emergencies, and planning for healthcare needs. This can lead to more prudent spending and investment in health-related expenses.